Uji Validitas Dan Reliabilitas Kuesioner Fonseca Anamnestic Index Versi Bahasa Indonesia Populasi Usia 19-21 Tahun (Penelitian) - Nadhira Razaqa Shabila; Ariel Jason; Carolina Marpaung (Jurnal Kedokteran Gigi Terpadu, 2020)
Background: Temporomandibular disorders are disorders that can involve masticatory muscles, temporomandibular joints, or both. The main symptoms and signs of temporomandibular disorders can be pain in the mastication muscle, pain in the temporomandibular joint area, limited movement of the jaw, and sounds in the temporomandibular joint, such as clicks or crepitus. Objective: To know the validity and reliability test of the Indonesian version of the Fonseca Anamnestic Index questionnaire in population ages 19-21 years in temporomandibular disorders. Methods: Observational analytic with cross-sectional study design. This study used a questionnaire with ten questions distributed via Google forms to 354 respondents (213 women and 141 men) aged 19-21 years in Jabodetabek. Validity test data were analyzed using correlation, and reliability test data were analyzed using Cronbach’s alpha. Results: The correlation test showed that the Indonesian version of the FAI questionnaire was valid with r > 0.1 and the results of the reliability test on the pain group were reliable with Cronbach's alpha > 0.6, but the results were unreliable in the non-pain group with Cronbach's alpha < 0.6. Conclusion: The Indonesian version of the FAI questionnaire was valid with a high correlation. Based on the pain group, the Indonesian version of the FAI questionnaire is reliable, while based on the non-pain group, the Indonesian version of the FAI questionnaire is not reliable.